Case Report: Management of a case of multidrug-resistant Klebsiella pneumoniae infection in a second-kidney transplant patient - Shettar, Supreeta R.; Sumana, Mahadevaiah Neelambike; Shetty, Manjunath S.; Maheshwarappa, Yogeesh D.; Raghukanth, Reddy G.; Srinivasan, Asha; Vamshi, Dharan P.; Kalyatanda, Gautam; Veerabhadra, Swamy G. S.; Chinchana, Shylaja Eshwarappa (Frontiers in Transplantation, 2025)
This case report on recurrent urinary tract infections (UTIs) caused by multidrug-resistant (MDR) Klebsiella pneumoniae in a post-renal transplant patient underscores the significant clinical challenge of managing MDR infections in immunocompromised individuals, particularly in the context of renal transplantation. The patient was treated with an extended infusion of meropenem, which offers prolonged drug exposure and enhances bactericidal activity against MDR pathogens. This approach is critical in overcoming the resistance mechanisms inherent to Klebsiella pneumoniae, thereby improving the likelihood of therapeutic success. The findings presented here highlight the potential efficacy of extended meropenem infusion in treating MDR infections, providing a valuable therapeutic option for clinicians facing similar cases. This report contributes to the growing evidence supporting advanced antibiotic administration techniques in managing complicated urinary tract infections in transplant in resource limited countries.